N-terminal domain of Schmallenberg virus envelope protein Gc delivered by recombinant equine herpesvirus type 1 and modified vaccinia virus Ankara: Immunogenicity and protective efficacy in cattle. Issue 34 (16th August 2018) - Wernike, Kerstin; Mundt, Alice; Link, Ellen Kathrin; Aebischer, Andrea; Schlotthauer, Felicia; Sutter, Gerd; Fux, Robert; Beer, Martin
Highlights: EHV-1- and MVA-based vector vaccines were generated to protect from SBV-infection. Both vectors expressed the N-terminal 234 amino acids of SBV-Gc. 2 of 4 animals of the EHV-1 group were protected from virulent SBV challenge. The MVA-based vaccine conferred complete protection in all immunized animal. Both vector vaccines are DIVA-compatible and allow an SBV marker vaccination concept. Abstract: Schmallenberg virus (SBV), which emerged in 2011 in Central Europe and subsequently spread very rapidly throughout the continent, affects predominantly ruminants. SBV is transmitted by insect vectors, and therefore vaccination is one of the major tools of disease control. Only recently, a domain connected to virus neutralization has been identified at the amino-terminal part of the viral envelope protein Gc. Here, this Gc domain delivered by recombinant EHV-1 or MVA vector viruses was tested in a vaccination-challenge trial in cattle, one of the major target species of SBV. The EHV-1-based vaccine conferred protection in two of four animals, whereas immunization using the MVA vector vaccine efficiently induced an SBV-specific antibody response and full protection against SBV challenge infection in all the vaccinated animals. Moreover, due to the absence of antibodies against SBVs N-protein, both vector vaccines enable the differentiation between vaccinated and field-infected animals making them to a promising tool to control SBV spread as well as to prevent disease in domestic ruminants.